Patience Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Waiting is not easy, whether it’s waiting to play with a toy or to eat a snack. And Little Kangaroo, Little Cat, and their friends are just not sure that they can be patient. But as their grown-ups show them, being patient doesn’t have to be boring or unbearable. There are many fun things they can do while they wait! C
Keywords: dept.lib